EPISTEMOLOGI DAKWAH PERSPEKTIF KH. CHARIRI SHOFA - Sugeng Riyadi; Ahmad Luthfi Hamidi (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
The study of the da'wah epistemology from the perspective of KH. Chariri Shofa reveals the concept of thoughts, struggles, masterpieces, and role-model aspects. This typical religious intellectual scholar with his magnum opus of the book